“Que macaco é esse?" Aplicativo para identificação dos primatas do Estado de São Paulo - Machado, Maria Clara Ariki (Universidade Federal de São Carlos, 2026)
In the face of human threats to biodiversity and the impacts of anthropogenic actions on wildlife, the need to preserve ecosystems as a whole has become increasingly evident. Based on the idea that “we only protect what we know and what we care about,” an important step toward the conservation of primate diversity in the state of São Paulo was taken with the enactment of Normative Ordinance FF/DE No. 324/2020, which regulates the practice of primate watching (Monkey Watching) within São Paulo State Protected Areas (Unidades de Conservação – UCs). This ordinance opens new pathways for increasing knowledge about the species present in the state. Within this context, and with the aim of contributing to the objectives established in the Action Plan for the Conservation of Primates in the State of São Paulo, the National Action Plan for the Conservation of Atlantic Forest Primates and the Maned Sloth, and consequently to the conservation of primate species and their habitats, a smartphone application was developed to assist in the identification of primates in outdoor observation activities within the state of São Paulo. This is made possible through the app’s comprehensive content, which includes photographs and information on the species, their biology, the biomes they inhabit, as well as thematic sections such as “Threats,” “Why we should not feed monkeys,” and “Why monkeys are not pets”. For validation purposes, the application was tested and an evaluation questionnaire was administered in five state protected areas managed by Fundação Florestal: (1) Angatuba Ecological Station; (2) Caetetus Ecological Station; (3) Juréia-Itatins Ecological Station; (4) Carlos Botelho State Park, and (5) Morro do Diabo State Park. In total, 33 individuals—including university students, high school students, and employees of Fundação Florestal—tested the application during primate observation activities and completed a perception questionnaire regarding the final product of this project. All participants stated that the app helped them obtain information about primates and, in fact, assisted them in identifying specimens. Some contributed by suggesting the use of simpler terms that could be understood by users unfamiliar with the subject. Furthermore, participants emphasized the importance of addressing sensitive topics such as why primates are not pets, highlighting the product's relevance.
"What monkey is that?” Identification app of São Paulo State primates
Keywords: Conservação; Biodiversidade; Observação de Fauna; Unidades de Conservação; Conservation; Biodiversity; Observation; Conservation Units; CIENCIAS BIOLOGICAS::ZOOLOGIA; 13. Ação contra a Mudança Global do Clima; 15. Vida Terrestre